2018
DOI: 10.1109/tvt.2018.2832845
|View full text |Cite
|
Sign up to set email alerts
|

Supervised-Learning-Aided Communication Framework for MIMO Systems With Low-Resolution ADCs

Abstract: This paper considers a massive multiple-inputmultiple-output (MIMO) system with low-resolution analog-todigital converters (ADCs). In this system, inspired by supervised learning, we propose a novel communication framework that consists of channel training and data detection. The underlying idea of the proposed framework is to use the input-output relations of a nonlinear system, formed by a channel and a quantization at the ADCs, for data detection. Specifically, for the channel training, we develop implicit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 39 publications
(90 reference statements)
0
103
0
Order By: Relevance
“…The work in [34] showed that if the transmitter employs QAM modulation and the quantization function satisfies Q b (−r) = −Q b (r) ∀r ∈ R, then the length of the training sequence can be reduced to T t = KL t /4. In Proposition 1 below, we generalize this result for any modulation scheme.…”
Section: B Subspace Training Methodsmentioning
confidence: 99%
“…The work in [34] showed that if the transmitter employs QAM modulation and the quantization function satisfies Q b (−r) = −Q b (r) ∀r ∈ R, then the length of the training sequence can be reduced to T t = KL t /4. In Proposition 1 below, we generalize this result for any modulation scheme.…”
Section: B Subspace Training Methodsmentioning
confidence: 99%
“…There have been increasing research interests in exploiting machine learning tools to address the nonlinearity of a MIMO system with low-resolution ADCs. By treating an end-to-end nonlinear MIMO system with low-resolution ADCs as an autoencoder, a supervised-learning aided communication framework was proposed in [17]. Specifically, it empirically learns the nonlinear channel (i.e., the conditional probability mass functions (PMFs)) by sending pilot symbols (or known data symbols) repeatedly.…”
Section: A Related Workmentioning
confidence: 99%
“…In this section, we propose a novel communication framework for the nonlinear multi-hop MU-MIMO relay channel by harnessing an end-to-end supervised-learning technique. We first present a simple model that can be a good approximation of the complicated nonlinear multi-hop MU-MIMO relay channel by exploiting a coding theoretical framework developed in our prior works [14], [17]. Then, we explain how to learn the model parameters using a simple training strategy and to detect the data symbols using the trained model parameters.…”
Section: Model-based Supervised-learning Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In [15], channel correlation is exploited by deep convolutional neural network (CNN) to improve the channel estimation accuracy and to reduce the computational complexity for millimeter wave massive MIMO systems. In [16], a supervised learning based successive interference cancellation is developed for MIMO detection with low-resolution ADCs. More results on DL for physical layer communications can be found in [12].…”
mentioning
confidence: 99%